(untitled) (LIS TODAY, 2026)
Libraries cannot be exclusively associated with physical books or printed materials anymore due to the emergence of the digital era. Libraries have, therefore, shifted to carrying enormous volumes of digital materials such as e-books and research articles. Considering further that the amount of data is increasing even faster and traditional search engines are becoming ineffective, new systems of information organization must be delivered. Knowledge graphs present such systems and assist in how information is categorized and searched. Since different databases are closely linked and related concepts are interlinked, knowledge graphs improve search results and offer access to relevant information more efficiently. The purpose of this present study is to demonstrate the transformation that takes place in librarians’ worldviews thanks to knowledge graphs. It does so by reviewing their design, advantages, and possible use. Issues of knowledge extraction, knowledge representation, and subsystem development in mass information systems are considered, as well as perspectives on their evolution.